The Impact of the COVID-19 Pandemic on Student Learning Motivation - Suarsi, Putu Dharma Komala; Wibawa, I Made Citra; Rati, Ni Wayan (Jurnal Ilmiah Sekolah Dasar, 2021)
The COVID-19 pandemic has had an impact in various fields, including education. One of the government's efforts to break the chain of spreading COVID-19 is to carry out learning activities online for all levels of education. This study aims to analyze the impact of the COVID-19 pandemic on the learning motivation of fourth grade elementary school students. This type of research is descriptive research, with quantitative and qualitative techniques. The population of this study were all fourth grade students in elementary school, amounting to 186 students. Determination of the sample using saturated sample technique so that the sample used is 186 students. The research data were obtained using the non-test method, namely with interview guidelines and instruments in the form of a Likert scale questionnaire for student learning motivation. The research data were analyzed using descriptive statistical analysis methods. Based on the results of the analysis, it was found that the learning process in grade IV SD during the COVID-19 pandemic was carried out in a combination of online and offline. Analysis of the motivation questionnaire data showed that the average student motivation, namely 79.71, was in the low / low category. So, it can be concluded that the COVID-19 pandemic has a negative impact on student learning motivation.